2020
DOI: 10.1177/1758155920968991
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and variation of neuropeptide Y in the brain of native Thai chicken

Abstract: Neuropeptide Y (NPY) plays a pivotal role in food intake and body weight regulation in both birds and mammals. Unlike imported broilers and layers, native Thai chicken, a tropical non-seasonal breeding species, has lower body weight and exhibits strongly maternal behaviors which, in turn, affect feeding behavior during the reproductive cycle. The aim of this study was to investigate the role(s) of NPY that might be associated with the reproductive cycle of female native Thai chickens using immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 63 publications
(100 reference statements)
6
13
0
Order By: Relevance
“…In this study, the primary and secondary antibodies used for detecting TH immunoreactivity were primary mouse ImmunoResearch Laboratories, Inc., West Grove, PA, USA) at 1:500 dilution with PBS, respectively. TH immunoreactivity using these antibodies has been previously described [26][27][28]42].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the primary and secondary antibodies used for detecting TH immunoreactivity were primary mouse ImmunoResearch Laboratories, Inc., West Grove, PA, USA) at 1:500 dilution with PBS, respectively. TH immunoreactivity using these antibodies has been previously described [26][27][28]42].…”
Section: Methodsmentioning
confidence: 99%
“…It expresses strong maternal behaviors which are inherited from the ancestor, the wild jungle fowl in Southeast Asia [36][37][38][39]. It is well documented that the neuroendocrine regulation of reproductive cycle and maternal behaviors are associated with GnRH, VIP, DA, PRL, MT, and neuropeptide Y in the female native Thai chickens [5,29,[40][41][42][43]. Presently, the neuroendocrine regulation of reproductive behaviors has been extensively studied in female native Thai chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the female native Thai chickens, NPY-ir neurons and fibers are extensively distributed throughout the brain. The numbers of NPY-ir neurons within the PVN are low in non-egg laying and egg-laying stages and then markedly increase during incubating eggs and rearing chick stages and changes in body weight are found in the opposite direction of changes in the numbers of NPY-ir neurons across the reproductive stages [28]. Moreover, it has been suggested that the numbers of NPY-ir neurons within the PVN play a pivotal role in the transition from incubating to rearing behavior in the female native Thai chickens [29].…”
Section: Introductionmentioning
confidence: 95%
“…In birds, NPY is one of the most potent orexigenic regulators of food intake [5,[19][20][21][22]. Food deprivation enhances expression of NPY mRNA [23], neuron activity [24], and NPY contents in the nucleus paraventricularis magnocellularis (paraventricular nucleus; PVN) [25][26][27] NPY is involved in the regulation of the reproductive cycle and maternal behaviors in female native Thai chickens [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation